Model-Model Pengembangan Kurikulum Pendidikan Agama Islam dan Faktor-Faktor Penyertanya - Khoirul Umam (Menara Tebuireng, 2018)
Islamic Religious Education (IRE) is a conscious effort aimed at guiding children so that they become true Muslims, firm faith, good deeds, and noble character, as well as useful to society, religion and the state. To achieve this goal a curriculum is needed. There are four curriculum development models that can be used for IRE, namely: (1) administrative model, (2) grass roots model, (3) Hilda Taba model, (4) Rogers model, and (5) Ralp Tyler model. Rogers’s curriculum development model is the most detailed and flexible model because it provides a ranking of four models from the simplest to the most perfect. There are a number of factors that accompany and follow curriculum development. Supporting factors include higher education, society, and value systems that develop in the community concerned. Moderate inhibiting factors are lack of time, lack of conformity of opinion both among fellow teachers and with principals and administrators, and the limitations of teacher skills and knowledge